2015
DOI: 10.1016/j.burns.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of burn on serum concentrations of sclerostin and FGF23

Abstract: Severe burn injury results in acute bone resorption followed by an adynamic state, most likely due to changes brought about by the inflammatory and glucocorticoid responses to the injury. There is a consequent increase in annual extrapolated fracture incidence in children. While osteoblasts have been reported to disappear from the bone surface and stem cell differentiation into osteoblasts is impaired, the effect of burns on osteocyte function is unknown. We measured serum concentrations of two osteocyte prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Although it is not clear at what serum concentration sclerostin begins to impair osteoblastogenesis as a result of interference with the Wnt signaling pathway, the rise in sclerostin is consistent with an increase in bone mass and possibly an increase in osteocytes. In contrast to the rise in sclerostin, serum FGF23 remained undetectable in pediatric patients given pamidronate as well as those who served as placebo controls . Therefore, something was suppressing FGF23 in both groups.…”
Section: Increased Phosphate Retentionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although it is not clear at what serum concentration sclerostin begins to impair osteoblastogenesis as a result of interference with the Wnt signaling pathway, the rise in sclerostin is consistent with an increase in bone mass and possibly an increase in osteocytes. In contrast to the rise in sclerostin, serum FGF23 remained undetectable in pediatric patients given pamidronate as well as those who served as placebo controls . Therefore, something was suppressing FGF23 in both groups.…”
Section: Increased Phosphate Retentionmentioning
confidence: 86%
“…Further studies of proteins produced by the osteocyte, fibroblast growth factor 23 (FGF 23) and sclerostin, in patients who had entered a randomized, prospective, double‐blind trial of a single dose of the bisphosphonate pamidronate within the first 10 days after burn injury revealed an interesting pattern. In placebo controls, serum concentrations of both FGF23 and sclerostin were undetectable . However, when samples were taken over time, the placebo controls demonstrated persistent low‐serum sclerostin concentrations, whereas those who had received pamidronate experienced a progressive rise in sclerostin concentration.…”
Section: Increased Phosphate Retentionmentioning
confidence: 98%
“…On the other hand, is possible that exercise with and without WBV may not be sufficient to overcome the physiological state triggered by burn injuries. Although we did not measure osteocyte activity, Klein and coworkers have postulated that, in burned children, osteocytes are abnormally low to absent, and hence increases in bone mass due to any exercise intervention may be difficult to obtain [35, 36]. Future studies are needed definitively determine the effectiveness of WBV on bone loss as well as to define cellular responses to exercise interventions with the goal of understanding the mechanisms underlying bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Severe burn results in acute bone resorption followed by a dynamic state, most likely due to changes brought about by the inflammatory and glucocorticoid responses to the injury (Klein et al, 2015). Recent studies found increased FGF23 in adult burn patient, suggesting that osteocytes may be apoptotic (Klein et al, 2015;Rousseau, 2015).…”
Section: Burnsmentioning
confidence: 99%